Penyuluhan Kesehatan Tentang Penyakit Gastritis pada Mahasiswa Prodi MIK STIKes Santa Elisabeth Medan Tahun 2023 - Pomarida Simbolon; Robin Bastian Waruwu; Grace Putri Laia; Ita Monita Munthe (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Healthy living habits must be instilled from an early age starting from oneself and unhealthy lifestyle changes must be reorganized to avoid the possibility of disease, one of which is gastritis. Gastritis is a disease that triggers an infection that occurs in the gastric mucosa caused by Mycobacterium and Helicobacter pylori, usually characterized by nausea, vomiting, pain in the pit of the stomach, and also headaches. Students are vulnerable to suffering from gastritis because students' daily lives are busy with lectures and assignments, so they tend to pay less attention to the food they consume, both the pattern and type of food. In efforts to prevent, the role of health implementation is very important, namely by providing health education to students. Health education is the first level of prevention carried out to reorganize unhealthy living habits. This research aims to increase the knowledge of MIK STIKes Santa Elisabeth Medan study program students about gastritis. This health education activity is carried out using lecture and discussion methods. The results of the activity showed that there was a difference in the average knowledge score before and after health education was implemented. The conclusion of this health education activity is that there has been an increase in the knowledge of MIK STIKes Santa Elisabeth Medan study program students by 29.87 points, so it is hoped that increasing knowledge can change student behavior, especially about how to prevent gastritis.